Genetic basis for T cell recognition of a major histocompatibility complex class II-restricted neo-self peptide (The Rockefeller University Press, 1995)
We have analyzed the genetic basis for T cell recognition of an endogenous major histocompatibility complex class II-restricted self peptide. Transgenic mice expressing the influenza virus PR8 hemagglutinin I-Ed-restricted determinant S1 (HA Tg mice) mediate negative selection of PR8 S1-specific T cells, but respond to immunization with a virus containing a closely related analogue, S1(K113). Sequence analysis of S1(K113)-specific T cell receptors (TCR) from nontransgenic mice revealed a dominant TCR clonotype that cross- reacts with PR8 S1. This clonotype is eliminated by negative selection in HA Tg mice; nonetheless, modified versions of this TCR that used altered junctional sequences and a novel V alpha/V beta pairing to evade negative selection by the S1 self peptide were identified. The remaining S1(K113)-specific TCRs from HA Tg mice were highly diverse; 13 of 15 S1(K113)-specific TCRs from HA Tg mice used unique V alpha/V beta pairings. Thus, tolerance to PR8 S1 as a self peptide does not limit the diversity of the T cell response to S1(K113).